P94 Effect of Hydroxyurea on Nocturnal and Awake Oxygen Saturation in Children with Sickle Cell Disease. (12th November 2015) - van Geyzel, L; Singh, B; Akthar, M; Ruiz, G; Inusa, B; Rees, D; Gupta, A
Abstract : Introduction: Sickle cell disease (SCD) causes lifelong morbidity and reduced life expectancy. Resting hypoxaemia and intermittent nocturnal oxygen desaturation are often seen in children with SCD, which may contribute to morbidity associated with vaso-occlusive episodes. Treatment with hydroxyurea reduces the frequency and severity of vaso-occlusive episodes 1 but the impact of hydroxyurea on oxygen saturation and sleep apnoea is unknown. Objective: To look for any difference in baseline oxygen saturation asleep and awake and the frequency of intermittent nocturnal desaturation after starting hydroxyurea in children with SCD. Methods: A retrospective review of children who were commenced on hydroxyurea between March 2006 and July 2014 attending two UK sickle-respiratory clinics. Data was collected from overnight sleep studies and averaged pulse oximeter spot check recordings in clinic notes when awake from a) 6 months before starting hydroxyurea and b) up to 2 years after. Lung function and haemoglobin changes were also noted over the same time periods. Results: Forty six children (25 male) with a median age of 10 years (range 5–19 years) were started on hydroxyurea. Haemoglobin and HbF rose significantly on hydroxyurea as expected (Table 1 ). After starting hydroxyurea the average overnight oxygen saturation increased from median of 93.5% to 95.2% (p = 0.01) and the median daytime spot oxygen saturation rose from 93.5% to 96.3% (p = 0.001). There was no significant change in the median intermittent nocturnal 3% oxygen desaturation index (ODI), nocturnal PCO2 or spirometry. Conclusion: In children with SCD, the use of hydroxyurea was associated with a significant increase in awake and nocturnal baseline oxygen saturation, but no change in intermittent nocturnal desaturation indices or lung function. This preliminary data suggests that improving oxygen saturation may be an important outcome of hydroxyurea therapy with potential benefits in reducing not only vaso-occlusive crises but future respiratory morbidities. This hypothesis would need to be tested by a prospective multicenter trial. Reference: 1 Charache S, Terrin ML, Moore RD, et al . Effect of hydroxyurea on the frequency of painful crises in sickle cell anemia. Investigators of the Multicenter Study of Hydroxyurea in Sickle Cell Anemia. N Engl J Med 1995;332 :1317–1322